How to Accurately Delineate Morphologically Conserved Taxa and Diagnose Their Phenotypic Disparities: Species Delimitation in Cryptic Rhinolophidae (Chiroptera) - Chornelia, Ada; Lu, Jianmei; Hughes, Alice Catherine (Frontiers in Ecology and Evolution, 2022)
Systematics and taxonomy are the backbone of all components of biology and ecology, yet cryptic species present a major challenge for accurate species identification. This is especially problematic as they represent a substantial portion of undiscovered biodiversity, and have implications for not only species conservation, but even assaying potential risk of zoonotic spillover. Here, we use integrative approaches to delineate potential cryptic species in horseshoe bats (Rhinolophidae), evaluate the phenotypic disparities between cryptic species, and identify key traits for their identification. We tested the use of multispecies coalescent models (MSC) using Bayesian Phylogenetic and Phylogeography (BPP) and found that BPP was useful in delineating potential cryptic species, and consistent with acoustic traits. Our results show that around 40% of Asian rhinolophid species are potentially cryptic and have not been formally described. In order to avoid potential misidentification and allow species to be accurately identified, we identified quantitative noseleaf sella and acoustic characters as the most informative traits in delineating between potential cryptic species in Rhinolophidae. This highlights the physical differences between cryptic species that are apparent in noseleaf traits which often only qualitatively described but rarely measured. Each part of the noseleaf including the sella, lateral lappets, and lancet furrows, play roles in focusing acoustic beams and thus, provide useful characteristics to identify cryptic Rhinolophus species. Finally, species delimitation for cryptic species cannot rely on genetic data alone, but such data should be complemented by other evidence, including phenotypic, acoustic data, and geographic distributions to ensure accurate species identification and delineation.